Universal credit and COVID-19 - Bennett, F (Child Poverty Action Group, 2020)
An anonymous civil servant was quoted in the press on 26 March as saying that the coronavirus crisis ‘could be the making of universal credit’. What has happened in recent months to universal credit (UC), which has been seen as the key answer in terms of benefits to difficulties during the COVID-19 crisis?